Distribution, fishery and some features of biology for Sclerocrangon salebrosa and Argis lar (Caridea, Crangonidae) in the northwestern Okhotsk Sea - D. N. Yuriev; V. S. Lukyanov; A. Yu. Povarov (Известия ТИНРО, 2020)
Trawl fishery of shrimps Sclerocrangon salebrosa and Argis lar in the Sakhalin Bay of the Okhotsk Sea has started in 2014 and develops rapidly. Meanwhile, spatial distribution of these species is not known well and their biology and stock dynamics are not studied. State of the fishery and distribution patterns of S. salebrosa and A. lar in the northwestern Okhotsk Sea are investigated on the data collected by the authors aboaed commercial fishing vessels and in the accounting trawl survey conducted aboard RV Dmitry Peskov in summer of 2019, as well as some features of their biology are considered. In total, 542 commercial trawl catches collected in 2015–2019 with horizontal opening 36 m from the depth of 39–140 m and 147 trawl catches collected during the survey with horizontal opening 16 m from the depth of 11–321 m are analyzed; 21,590 shrimp specimens caught within the period from June 23 to November 2 are examined. During 2014–2019, the number of shrimp fishing vessels in the Sakhalin Bay has increased from 1 to 6, their annual landing — from 78.7 to 642.0 t (376 t of S. salebrosa and 266 t of A. lar in 2019). Their mean catch per unit effort varied from 48 to 108 kg/hr of trawling for S. salebrosa and from 40 to 87 kg/hr for A. lar, with the average catch per trawling 379 and 346 kg, and average daily catch 1380 and 1144 kg, respectively. Night catches of S. salebrosa were in 2.7 times higher than the daily catches, on average (104.7 ± 45.7 kg/hr vs 39.1 ± 31.8 kg/hr); night catches of A. lar were in 2.0 times higher than the daily catches (80.2 ± 39.0 kg/hr vs 39.6 ± 34.2 kg/hr). Portion of A. lar in the summary catches of two species varied from 4 to 88 %, on average 48 %; besides, by-catch of fish (flounders, saffron cod, pollock, cod, sculpins, herring) and humpy shrimp Pandalus goniurus was considerable. So, the portion of the most valuable species (sculptured shrimp S. salebrosa) did not exceed ⅓ of the total catch, on average. The actual annual catches exceeded significantly the recommended volumes in 2017–2019, up to 164 % for S. salebrosa and 156 % for A. lar. According to results of the trawl survey in 2019, spatial distribution patterns for S. salebrosa and A. lar coincide in details in the northern Okhotsk Sea: both species are distributed at the depth between 20–145 m, with the densest aggregations (> 60 % of both stocks) located between Bolshoi Shantar Island and the northern tip of Sakhalin, southward from 55о 30′ N, where their biomasses reach 434 kg/km2 for S. salebrosa and 68 kg/km2 for A. lar. Total commercial stocks of these species within the North Okhotsk Sea fishery district were assessed in 2019 as 16.0 . 103 t for S. salebrosa and 3.8 . 103 t for A. lar. Reproductive cycles of S. salebrosa and A. lar females in the Okhotsk Sea are fundamentally the same as the cycle of former species in Peter the Great Bay (Japan Sea), with their total duration of 48 months including 24 months for the gonads development until spawning and 24 months from the spawning to hatching of larvae. In the Okhotsk Sea, spawning of S. salebrosa and A. lar occurs most likely in spring; mass hatching of their larvae — in summer.